Il pallone assente. Calcio, giochi nei libri di lettura per la scuola elementare tra il 1945 e il 1970 - Walter Fochesato (Studi sulla Formazione)
The paper examines how between 1945 and the first half of the 1970s, football and, more generally, sport was mentioned in textbooks for primary school. For a long time this aspect was either completely ignored or served to admonish and show what the risks of playing in the street are: from colds, to peelings to not infrequently tragic and lethal outcomes. Outdoor games are viewed with pedagogical suspicion and even the simple route between home and school is fraught with danger if one does not behave correctly. Then slowly, around the mid-1960s, textbooks saw timid signs of renewal but prejudices, cautions and rules to conform to did not cease.